One child reading : my auto-bibliography - Mackey, Margaret, 1948- (The University of Alberta Press, 2016)
"In a significant and unique contribution to our understanding of reading and literacy development, Margaret Mackey draws together memory, textual criticism, social analysis, and reading theory in an extraordinary act of self-study. One Child Reading reflects a remarkable academic undertaking. Seeking a deeper sense of what happens when we read, Mackey revisited the texts she read, viewed, listened to, and played as she became literate in the 1950s and 1960s in St. John's, Newfoundland. This tremendous sweep of reading included school texts, knitting patterns, and games, as well as hundreds of books. The result is not a memoir but rather a deftly theorized exploration of how a reader is constructed. This is an essential book for librarians, classroom teachers, those involved in literacy development, and all serious readers."--